2020
DOI: 10.1128/jvi.00474-20
|View full text |Cite
|
Sign up to set email alerts
|

UL88 Mediates the Incorporation of a Subset of Proteins into the Virion Tegument

Abstract: Little is known about the human cytomegalovirus (HCMV) tegument protein UL88. Large-scale genomic studies have reported disparate results for UL88-null viruses, reporting both no phenotype and a >1-log decrease in virus titers. UL88 has also been reported to interact with UL69 and UL48, but the functional relevance of this interaction is unknown. Here, we report that UL88, which is conserved among different viral strains, is dispensable for production of infectious HCMV virions in multiple HCMV strains and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Some tegument genes were also found to be vPIC-regulated, including the capsid-associated UL32 ( Yu et al., 2017 ), the early acting virion cargo tegument UL48 ( Kwon et al., 2017 ; Wang et al., 2006 ), and envelopment and egress-associated UL99 and UL103 ( Figure 5 C) ( Ahlqvist and Mocarski, 2011 ; Sanchez et al., 2000 ; Seo and Britt, 2006 ; Silva et al., 2003 ). In contrast, we found that tegument genes UL25 ( Battista et al., 1999 ), UL26 ( Mathers et al., 2014 ; Munger et al., 2006 ), UL83 ( Kalejta, 2008 ), and UL88 ( Kumar et al., 2020 ) were not regulated by the vPIC ( Figure S2 D). Moreover, UL26, UL83, UL86/MCP, and UL99 exhibit similar late expression kinetics over the course of infection ( Weekes et al., 2014 ), but only UL86 and UL99 are regulated by the vPIC ( Figures 2 B, 3 A-3G, 5 C and S2 D).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Some tegument genes were also found to be vPIC-regulated, including the capsid-associated UL32 ( Yu et al., 2017 ), the early acting virion cargo tegument UL48 ( Kwon et al., 2017 ; Wang et al., 2006 ), and envelopment and egress-associated UL99 and UL103 ( Figure 5 C) ( Ahlqvist and Mocarski, 2011 ; Sanchez et al., 2000 ; Seo and Britt, 2006 ; Silva et al., 2003 ). In contrast, we found that tegument genes UL25 ( Battista et al., 1999 ), UL26 ( Mathers et al., 2014 ; Munger et al., 2006 ), UL83 ( Kalejta, 2008 ), and UL88 ( Kumar et al., 2020 ) were not regulated by the vPIC ( Figure S2 D). Moreover, UL26, UL83, UL86/MCP, and UL99 exhibit similar late expression kinetics over the course of infection ( Weekes et al., 2014 ), but only UL86 and UL99 are regulated by the vPIC ( Figures 2 B, 3 A-3G, 5 C and S2 D).…”
Section: Discussionmentioning
confidence: 79%
“…A similar analysis of genes in cluster III revealed that 29% are classified as late (class 5) ( Figures 5 E and S2 D), and only 36% of genes encode virion cargo ( Figures 5 F and S2 D). Notable examples of late genes that are not regulated by the vPIC include UL25 ( Battista et al., 1999 ), UL26 ( Mathers et al., 2014 ; Munger et al., 2006 ), the multifunctional UL83 ( Kalejta, 2008 ) and UL88 ( Kumar et al., 2020 ) ( Figure S2 D).…”
Section: Resultsmentioning
confidence: 99%
“…Cluster VI was enriched with non-essential tegument proteins with class five expression (late) and high virion enrichment. These included UL25 [ 42 ], UL82 [ 43 ], UL83 [ 13 ], and UL88 [ 44 ] ( Figure 1 A). Clusters IV and V grouped augmenting gene products with a diverse set of known functions ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
“…Only the smallest capsid protein UL48A, for which we detected relatively few cross-links, co-clusters with the tegument group of cluster 1. Besides UL48A, this subcluster contained typical inner tegument proteins like UL32 and UL48, that are characterized by their tight association to the nucleocapsid 3 as well as the UL48-associated protein UL47 27 ,UL82 (also known as pp71), the UL82 interactors UL35 28 and UL88, which are important for recruiting UL47, UL48 and UL82 into virions 29 . As UL82 and UL35 proteins traffic independently from the nucleocapsid upon infection 30, 31 , their allocation to the nucleocapsid-proximal tegument layer indicates that proximity to the nucleocapsid does not necessarily reflect tight attachment upon cell entry.…”
Section: Resultsmentioning
confidence: 99%